Batesian mimicry has evolved with deleterious effects of the pleiotropic gene doublesex - Shinya Komata (Nature Portfolio, 2020)
Abstract Dimorphic female-limited Batesian mimicry in the swallowtail butterfly Papilio polytes is regulated by the supergene locus H, harbouring the mimetic (H) and non-mimetic (h) doublesex (dsx) gene. In the present study, we demonstrated that dsx-H negatively affects the number of eggs laid, hatching rate, larval survival rate, and adult lifespan. When crossed with hh males, the number of eggs laid of mimetic females (genotype HH) was lower than that of non-mimetic females (hh). Moreover, hh and Hh females laid fewer eggs when crossed with HH males. The hatching and larval survival rates were lower when both female and male parents harboured dsx-H. The adult lifespan of HH females was shorter than that of hh females, while it was similar in males regardless of the genotype. These findings suggest the presence of a cost–benefit balance of Batesian mimicry, which is evolved to avoid predation but is accompanied by physiological deficits, in this species.